Factors Related to Community Forest Management Practices in Two Rural Villages in Nepal - Tamang, Devika (1990)
Implementation has been referred to as the achilles heel of reform in developing countries. The inability to implement policies and plans is the main cause of programme failure. The community forestry programmes in Nepal is a case which has encountered difficulty in implementation. With the general purpose of determining the factors that were related to community forest management practices, a comparative case study was conducted in two villages. One of the villages had good implementation of forest management practices and the other poor. The study was conducted in Hanspur and Dangsimarang Villages in Nepal. Using the stratified random sampling technique, a sample of 100 household heads (who were forest users) were chosen. An interview schedule was used to obtain the data. The findings of the study reported that there is a significant difference in forest management practices implemented in the study villages. The focus of the difference was the control exercised in limiting usage of forests in Hanspur Village. While in Dangsimarang Village, uncontrolled usage of forest had caused degradation. In addition, there were significant differences in participation in decisions and leadership functions, but there was no difference in physical variables. Participation in decisions and leadership emerged as variables that were more important than contributing towards collective implementation management practices. Variation in physical functions others in of forest variables were related to demand for forest products, but did not, in itself, contribute toward the collective implementation in the village. It was recommended that action should be taken to acknowledge and strengthen the forest management efforts undertaken by the forest users in the villages. Finally, additional research on forest management in Nepal is needed with less emphasis on trees and more on people who use, control, own, conserve and destroy forests.